TANTANGAN SOSIAL DI ERA DIGITAL PADA INTERAKSI MANUSIA - Siti Arbaina Juliana; Trisna Liza; Fatimahtuzzahra; Muhammad Akbar Hilmi Imel (Pusat Studi Ekonomi Publikasi Ilmiah dan Pengembangan SDM Azramedia indonesia, 2023)
With the rapid development of digital technology such as the internet, social media, and mobile devices, humans now have greater access to information and communication than ever before. This has changed the way humans interact. The digital era has brought about profound changes in the way humans interact. Rapidly developing information and communication technologies, such as social media, mobile devices and the internet, have influenced various aspects of social life. Human interaction is no longer limited to face-to-face meetings, but also via digital platforms. This brings a number of social challenges that need to be understood more deeply. The research method used in this research is a qualitative research method, namely the literature study method. Data collection techniques are based on various journal literature. This research intends to explore data through research journals and analyze it simultaneously. Information technology has an impact on people's lives, especially in society, resulting in many changes that will occur at any time and is a dynamic process. Information technology as a tool to help solve existing problems in society is expected to become a facility that can be useful or helpful. Information technology is also very important in society in terms of socializing and interacting. Information technology causes significant changes in people's lives in all their civilizations and cultures. Currently, technological advances such as telephones/cellphones and the internet are not only enjoyed by city people, but village people can also enjoy them. However, it cannot be denied that the presence of information technology has had an impact on people's social lives. The impact of information technology on social dynamics has several factors that influence the occurrence or elements that cause the social dynamics referred to above, namely in society.